Seed dispersal by the lek-forming white-bearded manakin (Manacus manacus, Pipridae) in the Brazilian Atlantic forest - Cestari, César [UNESP]; Pizo, Marco Aurélio [UNESP] (Cambridge University Press (CUP), 2013)
The movement patterns of males, females and juveniles of lekking species often differ due to differences in the commitment to lek activities, which may lead to differences in the spatial distribution and dispersal distances of seeds they eat. By sampling seeds in three lek and non-lek areas of the white-bearded manakin (Manacus manacus), we tested whether this lekking species increased the abundance and species richness of seeds in lek areas and, at a finer scale, in 21 displaying courts within lek areas. Combining data on seed defecation or regurgitation rates by free-ranging individuals, the number of seeds in droppings or regurgitations of mist-netted birds, and the distances travelled by birds equipped with radio-transmitters, we estimated the potential spatial distribution of seeds generated by six resident males and six females or juveniles during the morning peak of lek activity and when lek activity decreased in the afternoon. There was no difference in the species richness (46 and 44 morphospecies, respectively) and abundance of seeds (15.4 ± 7.3 seeds and 14.0 ± 1.1 seeds, respectively) between lek and non-lek areas. Within leks both parameters increased in courts (45 spp., 17.6 ± 14 seeds) compared with non-court sites (22 spp., 1.9 ± 1.8 seeds), likely as a consequence of the longer time spent by resident males in perches in or near display courts. Distances moved by juveniles and females per 60-min period (183 ± 272 m) were greater than resident males (42.6 ± 22.0 m) in the mornings, while the opposite happened in the afternoons (55.2 ± 40.7 m and 157 ± 105 m, respectively). We conclude that the spatial aggregation of seeds in lek areas of M. manacus occurs at the court level, and the spatial distribution of deposited seeds varies with manakin lekking status and the daily period of foraging. © Cambridge University Press 2013.
Keywords: frugivory; movement ecology; Neotropic; radio-telemetry; seed aggregation